Parent-informed test-control functional analysis and treatment of problem behavior related to combined establishing operations. (19th May 2017) - Strohmeier, Craig W.; Murphy, Ashley; O'Connor, Julia T.
ABSTRACT: Purpose : Analog functional analysis (FA) represents the gold standard practice in the functional assessment of problem behavior. In some cases, modifications to typical FA test conditions are required to isolate the environmental variables that evoke and maintain problem behavior. The purpose of the current study was to describe the development of an individualized FA test condition that included combined establishing operations (EOs). Methods : After an inconclusive standard FA, an individualized FA was conducted based on semi-structured descriptive assessment data collected by parents in the home setting. Results : The individualized test-control combined EO FA produced clearly differentiated results that informed a function-based treatment. Conclusions : Based on the results of the current study and other similar lines of contemporary research on FA methodology, strategies are discussed for gathering data to inform individualized FA test conditions and derived treatments.